(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article comprehensively analyzes the structural mechanics of literary text composition, detailing the interconnected roles of theme, idea, plot, conflict, and characterization. By evaluating qualitative narrative frameworks, it provides an academic model for modern literary analysis. (34 words)